New model for low-frequency noise in poly-Si resistors - Lee, J; Han, I; Chang, SK; Kim, E; Lee, MB (TRANS TECH PUBLICATIONS LTD, 2005)
This paper presents a simple and novel model for low-frequency noise generation in polycrystalline-Si resistors within the number fluctuation model. The grain boundary in polycrystalline-Si thin films is the major source of noise and is modeled as independent symmetric Schottky barriers in series, face-to-face. It has been found that trapping and detrapping of the carriers at the traps in the space charge region of the grain boundary via thermal activation modulate the barrier height and generate the low-frequency noise. The model successfully explains the experimental data and gives useful information about the defects in the space charge region of the grain boundary. As a result, the Hooge parameter is interpreted in terms of defect density, among other parameters.
Keywords: SCHOTTKY-BARRIER DIODES; 1/F NOISE; POLYSILICON RESISTORS; FLICKER NOISE